(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
“EP appears as a ‘black box’ – a unitary actor characterised by its sui generis nature and its continuous attempts to gain more influence inside the EU’s political system. However, the EP can also be understood as a ‘normal’ parliament – ‘part of the European political “establishment” – with its own internal politics and structures that need to be understood if one wishes to understand the role and influence of the EP in the wider political system.”